Experimental Research of Wireless Sensor Network Application in Aviation - Stankunas, J.; Rudinskas, D.; Lasauskas, E. (Elektronika ir Elektrotechnika, 2011)
The paper presents the application of wireless sensor networks in aviation for measuring and transferring flight parameters. IEEE 802.15.4 standard ZigBee of low price, which operates in the low range of the ISM frequency band, was chosen. Experiments were performed during free flight. Evaluation of measurement results using Kalman filtering algorithm is provided. Ill. 6, bibl. 10, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.353